Determination of the immunohistochemical characteristics of basal cell carcinoma and squamous cell carcinoma by Bax, Bcl-2 and Ki67 - Coskun, Basak Kandi; Cobanoglu, Bengu (Deri Zuhrevi Hastaliklar Dernegi, 2005)
Background and design:The present study aimed at investigating the expression characteristics of bax and Bcl-2 proteins as well as the relation between Ki67, known to be a proliferation marker, and the two tumors immunohistochemically. Material and method: Twenty squamous cell carcinoma (SCC) and 20 basal cell carcinoma (BCC) cases were evaluated by immunohistochemical method using bax, Bcl-2 and Ki67 antibodies. There were marked differences between Bax, Bcl-2 and Ki67 values in SCC and BCC. Result: An overall evaluation showed that Bcl-2 was highly positive, whereas Bax expression was ignorable in BCC. However, Bax was evidently positive in most SCC cases. Ki67 was positive at variable degrees in 90% of SCC cases, but only slightly positive in 10% of BCC cases. The fact that Bax positivity is more evident in SCC and Bcl-2 positivity in BCC demonstrates that apoptosis is more marked in SCC. Conclusion: This result suggests that although apoptosis is not strongly related with Bax in BCC, Bcl-2 gene family regulates apoptosis activity. In SCC cases with a more aggressive course, Ki67 was found high in relation to the degree of differentiation. However, number of literature studies addressing this topic is limited; therefore studies including a higher number of cases are needed.
Bazal hücreli karsinoma ile skuamoz hücreli karsinomanin histokimyasal özelliklerinin Bax, Bcl-2 ve Ki-67 ile belirlenmesi
Keywords: Basal cell carcinoma; squamous cell carcinoma; Bax; Bcl-2; Ki67